Persepsi Pembiayaan Simpan Pinjam dengan Pengembangan Modal Usaha Mikro Kecil dan Menengah (Studi Kasus Cabang Pegadaian Syariah Meulaboh Aceh Barat) - Maisuri, Maisuri; Sani, Sri Rosmiati (Regress: Journal of Economics & Management, 2023)
Microfinance plays a pivotal role in enhancing Micro, Small, and Medium Enterprises (MSMEs) in Aceh, contributing to business growth and economic development for the middle-income population. The availability of microfinance initiatives has proven beneficial to many middle-income individuals, fostering economic growth in the production of goods and services. Moreover, it contributes to economic development for the middle-income community while simultaneously reducing unemployment rates in West Aceh. This research aims to investigate the influence of microfinance on the establishment of Micro, Small, and Medium Enterprises. The study is conducted at the Pegadaian Meulaboh office, focusing on the Johan Pahlawan district. Motivated by a desire to gain deeper insights into the growth of MSMEs in the Johan Pahlawan area, the research utilizes primary data analysis. The research sample comprises independently operating MSMEs in the Johan Pahlawan district. The findings underscore the significant impact of microfinance funding on MSMEs in the Johan Pahlawan district, as indicated by the study's outcomes. This research contributes to the understanding of the role of microfinance in fostering the growth of MSMEs and the overall economic development in the region.